Cost-Effectiveness and Budget Impact Analysis of Apatinib for Advanced Metastatic Gastric Cancer from the Perspective of Health Insurance System - Yongrui Bai; Yuejuan Xu; Bin Wu (Gastroenterology Research and Practice)
Objective. This study evaluated the cost-effectiveness of apatinib in patients with chemotherapy-refractory mGC. Patients and Methods. A Markov model was developed to simulate the clinical course of typical patients with chemotherapy-refractory metastatic gastric cancer (mGC). We estimated the 10-year quality-adjusted life-years (QALY), costs, and incremental cost-effectiveness ratios (ICER). Model inputs were derived from the published literature and government sources. Direct costs were estimated from the perspective of the Chinese health insurance system. A scenario analysis for a Patient Assistance Programme (PAP) was performed. Results. Baseline analysis showed that apatinib increased the cost and QALYs by $7859 and 0.192, respectively, relative to conventional chemotherapy, resulting in an ICER of $40,997/QALY gained. When PAP was available, the ICER was $21,132/QALY. Probabilistic sensitivity analyses confirmed that apatinib with PAP achieved nearly 65% likelihood of cost-effectiveness at the threshold of $22,200. One-way sensitivity analyses demonstrated that the utility of progression-free survival was the most influential factor on the robustness of the model. Budget impact analysis estimated that the annual increase in fiscal expenditures would be approximately 0.45 million dollars. Conclusions. Our analysis suggests that apatinib is likely cost-effective in patients with chemotherapy-refractory mGC when PAP is available.